PENGEMBANGAN CRACKELS (CRACKERS TEPUNG LELE DAN KELOR) SUMBER ANTIOKSIDAN SEBAGAI ALTERNATIF CEMILAN IBU HAMIL DI MASA PANDEMI - Kustiani, Ai (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Background: The prevalence of anemic pregnant women in Indonesia in 2018 was still high which was at 48.9%.Â  Pregnant women are vulnerable to nutritional problems and other diseases, including being infected with the Covid-19 virus. One of the preventive measures is to eat nutritious foods such as foods that are a source of antioxidants. The use of crackels (catfish crackers and Moringa) as an alternative snack for pregnant women is the right step because crackels contain high nutrients. The research objectives were to develop crackels, to analyze the nutritional content and their organoleptic quality. Methods: This research is an experimental study with substitution treatment of Moringa leaf flour towards catfish crackers conducted at the Laboratory of Mitra Indonesia University and State Polytechnic of Lampung. Six treatments were done with four repetitions. Data analysis used Microsoft Excel 2007 and SPSS for windows version 20. The tests used were non-parametric statistical tests, Anova, and paired sample t test. Result: Crackels formula that has been developed with the best acceptance and quality was formula F1 (3.49) which was derived from the addition of 10 grams of Moringa leaf flour and 30 grams of catfish flour. The best nutritional content of crackels is namely, energy 403 kcal, protein 21.3%, fat 15%, carbohydrates 45.7%, iron 8.32 mg/100g, calcium 29.6 mg/100g, sodium 672 mg/100g, and antioxidants indicated by % inhibition ranging from 32- 35% and IC50 value of 68.34%. Conclusion: The best crackels was the crackels which contain 10 grams of Moringa leaf flour and 30 grams of catfish which are effective as sources of antioxidants for pregnant women with antioxidants indicated by % inhibition ranging from 32- 35% . Keywords: anemic pregnant mother, antioxidant, catfish, crackers, moringa